NADA BERITA DAN LITERASI MEDIA (ANALISIS ISI BERITA TENTANG PEMERINTAH KABUPATEN NGAWI, MADIUN DAN MAGETAN PADA RADAR MADIUN) - Wahono, Hari (Transformasi, 2017)
This research aim to describe the tone of the news about local government, editorialpolicy of Radar Madiun and media literacy. The tone of the news about local governmentwhich presented by Radar Madiun can be positif, negative or neutral, this depands onfactors which found in each local government.This reasearch combine both quantitative and qualitative methode, the locaition of thisreasearch are Ngawi regency, Madiun Regency and Magetan Regency. Sampels of thisresearch were news presented by Radar Madiun in which discuse about government dailyactivity and develpoment activity had been done by each regency. For detrminen the toneof the news, researcher refeer to idea which used by Stempel in Flournoy. Refeer to thatidea, the tone of the news presented by Radar Madiun can be positive, negative andneutral. Editoral policy of Radar Madiun infuenced by same foctors.The tone of the news presented by Radar Madiun in which discouse about dailygovernment activity in Ngawi regency was neutral tone, Madiun Regency was negativetone and neutral tone for Magetan Regency. In another side whan Radar Madiun discousethe develpoment activity had been done by Ngawi Regency the tone of the news wasnegative tone, positive tone for Madiun Regency and Neutral tone for Magetan Regency.In this research we found that editorial polecy of Radar Madiun influenced by somefactor,that are ediology, politic and social culture in which Radar Madiun coveredarea.The reader who have good media literacy can not be influenced by the tone of thenews presented bay the media, in the other side for the reader who not good enough inmedia literacy will influenced by that tone of the news.Keywords : news, the tone of the news, editorial policy